Preparing health professional students for interprofessional practice related to neurodevelopmental disabilities: a pilot program. Issue 2 (4th March 2023) - Lee, Meen Hye; Jones, Carolyn W.; White, Patricia; Johnson, Dan; Kim-Godwin, Yeoun Soo
ABSTRACT: Many health professional students have insufficient general knowledge about individuals with neurodevelopmental disabilities. Students lack the expertise required to work with this population and their families. Interprofessional practice education (IPE) programs, designed for working with individuals with specialized needs and their families, are needed to improve overall care provided. An IPE program related to neurodevelopmental disabilities for health professional students was implemented focusing on applied learning and community engagement to develop competencies for students related to neurodevelopmental disabilities at a state university in the U.S. The purpose of this research was to describe the development and implementation of an IPE program and to examine the effectiveness of the IPE program aimed at developing identified competencies and increase awareness related to care of individuals with ND for health professional students. The findings suggest the IPE program enhanced health professional students' perceived competencies to identify and provide culturally sensitive and family-centered care for individuals with neurodevelopmental disabilities and their families. This experience also provided an opportunity for personal/professional growth and increased awareness of the unique needs of these individuals with neurodevelopmental disabilities and their families.